Selective and sensitive electrochemical detection of the Human Epidermal Growth Receptor 2 breast cancer biomarker, using Co (II) phthalocyanine-nanoparticle based platforms - Centane, Sixolile Sibongiseni (Rhodes University, Faculty of Science, Department of Chemistry)
Breast cancer is the world's leading cause of cancer related deaths in women worldwide. The main reason lies in its late detection, mostly in the metastatic stage resulting in poor after-therapy prognosis, despite advances in methods of diagnosis and therapy. The reason for late-stage detection, is because breast cancer like any other cancers is asymptomatic in its early stages. Significant and characterizable features present in the later stages. Furthermore, conventional methods for breast cancer detection are more useful in the identification of the phenotypic features of cancer cells that arise at a later stage of the disease. Another issue with conventional methods where cancer diagnosis is concerned is that they tend to be specialist-dependent, time consuming and costly. Thus, easy, fast and inexpensive detection methods need to be developed urgently. Biomarker-based cancer diagnosis has emerged as one of the most promising strategies for early diagnosis, monitoring disease progression, and subsequent cancer treatment. This thesis focuses on the design and development of novel electrochemical biosensor platforms towards the low cost, efficient, sensitive and simple detection of early-stage breast cancer biomarker, human epidermal growth factor 2 (HER2). The electrochemical method is preferred because of its moderate cost, rapid response, ease of operation, readily quantifiable signal as well as high sensitivity and selectivity with lower detection limits. This thesis reports on two strategies towards signal amplification and sensitive detection of HER2, namely signal based amplification and target-based amplification. The former focuses on electrode or transducer modification techniques for improved signal to noise ratio. In which case; novel nanocomposites of phthalocyanines, graphene quantum dots, gold nanoparticles and cerium oxide nanoparticles are used for electrode modification for signal amplification and biorecognition element immobilization. The biorecognition elements of choice, are an aptamer and antibody known to be specific to the HER2 antigen for an enhanced sensor sensitivity and specificity. The second strategy focuses on increasing the number of detectable targets on the electrode surface towards enhanced sensitivity, precision and sensor accuracy. In which case; the performance of the aptamer and the antibody as recognition elements was explored. Furthermore, the effect of arrangement of these recognition elements on the electrode surface is investigated and reported upon. The strategies covered in this thesis are expected to result in novel biosensor platforms that can detect the HER2 biomarker with high precision, reproducibility, sensitivity and stability; towards low cost and effective early-stage breast cancer diagnostic tools.
Keywords: Electrochemical sensors; HER-2 protein; Breast Cancer; Biochemical markers; Phthalocyanines; Nanoparticles